Textbook Analysis for Enhancing Arabic Listening and Writing Skills - Said, Said Al Zaiim Bani; Hikmah, Khizanatul (Universitas Muhammadiyah Sidoarjo, 2024)
This study rigorously examines the content of maharah istima' wal kitabah (listening and writing skills) within the textbook